G325(P) An evaluation of our local paediatric epilepsy services. (12th March 2018) - Patel, LB; El Gamal, M; Murray, D; Nair, P
Abstract : Aims: 34, 000 Children and Young People (CYP) in England have a diagnosis of epilepsy and receive anti-epileptic drugs. NICE have described high-priority areas for quality improvement; The Epilepsy in CYP, Quality Standard (QS27). Our local service aims to provide an excellent multidisciplinary service to serve its patients and their families in a holistic manner. It is delivered by consultants, a specialist nurse, rotating junior doctors and the nursing team. Methods: To evaluate our current local service standard against national guidance and identify areas of possible improvement, we developed a Caregiver and Patient Reported Survey (CPRS). It covered both quality standards and expectations from patients and their parents and caregivers. Anonymous CPRS were disseminated in the waiting areas of our mutli-site outpatient paediatric epilepsy clinics over a 3 month period (n=44). Observational analyses were completed on all the returned CPRS and the results were mapped against national guidance. Results: Observational analyses revealed 70.5% of CPRS were completed by caregiver/parent and 22.7% by CYP (6.8% no return), 84.1% stated that they were satisfied-very satisfied with our services, 90.9% were happy-very happy with their clinical experience, 82.7% were happy- very happy with the support they received outside of the clinic environment (34.0% no return) and 77.8% were happy- very happy with the support received whilst inpatients (38.6% no return). Our patients had experienced problems in the educational, social and home lives due to epilepsy; 31.8% at school, 18.2% attending out of school clubs and 31.8% socialising. 18.2% of patients experienced problems with other areas including; side effects of medication, communication with services and behavioural issues. 90.2% were content with the information they received following diagnosis and 95.2% between appointments. 86% were happy to very happy with the verbal information and 81.4% with written information. 14% identified areas of change including; information on the effects of epilepsy on learning and education, more streamlined information and flexibility around access to services. Conclusion: Communication and information delivery were identified as key areas of possible improvement. We are now developing an electronic, locally tailored Paediatric Epilepsy Information Pack to be disseminated to patients and their families.